Segmentasi Kabupaten/Kota Berdasarkan Indikator Rumah Layak Huni di Provinsi Nusa Tenggara Timur Tahun 2024 - Marlia Augustio Adang (Badan Pusat Statistik Provinsi NTT, 2025)
Building from villages and from the ground up to achieve economic equality and eradicate poverty is one of the Asta Cita Missions of the Indonesian Government for the 2025 to 2029 period. To support the achievement of this mission, improving access to decent, affordable, and quality housing has become one of the Government’s key targets. Nusa Tenggara Timur is among the six provinces in Indonesia with the lowest percentage of households with access to decent housing. Therefore, to improve the province’s performance, a study needs to be conducted to accurately identify the target groups and support effective decision-making. This study aims to segment regencies/cities into several groups based on access to decent housing, serving as a reference for development priorities. The methodology used in this study is hierarchical cluster analysis, comparing the single linkage, average linkage, complete linkage, and Ward’s method. Among these, Ward's method yields the highest agglomerative coefficient and results in segmentation of regions into five distinct groups. The study concludes that policy-making based on regional prioritization through clustering analysis can improve the efficiency and effectiveness of programs aimed at ensuring decent, affordable, and quality housing for the community.